Soil pathogen communities associated with native and non‐native Phragmites australis populations in freshwater wetlands - Nelson, Eric B.; Karp, Mary Ann (Ecology and evolution, 2013)
Summary Soil pathogens are believed to be major contributors to negative plant–soil feedbacks that regulate plant community dynamics and plant invasions. While the theoretical basis for pathogen regulation of plant communities is well established within the plant–soil feedback framework, direct experimental evidence for pathogen community responses to plants has been limited, often relying largely on indirect evidence based on above‐ground plant responses. As a result, specific soil pathogen responses accompanying above‐ground plant community dynamics are largely unknown. Here, we examine the oomycete pathogens in soils conditioned by established populations of native noninvasive and non‐native invasive haplotypes of Phragmites australis (European common reed). Our aim was to assess whether populations of invasive plants harbor unique communities of pathogens that differ from those associated with noninvasive populations and whether the distribution of taxa within these communities may help to explain invasive success. We compared the composition and abundance of pathogenic and saprobic oomycete species over a 2‐year period. Despite a diversity of oomycete taxa detected in soils from both native and non‐native populations, pathogen communities from both invaded and noninvaded soils were dominated by species of Pythium. Pathogen species that contributed the most to the differences observed between invaded and noninvaded soils were distributed between invaded and noninvaded soils. However, the specific taxa in invaded soils responsible for community differences were distinct from those in noninvaded soils that contributed to community differences. Our results indicate that, despite the phylogenetic relatedness of native and non‐native P. australis haplotypes, pathogen communities associated with the dominant non‐native haplotype are distinct from those of the rare native haplotype. Pathogen taxa that dominate either noninvaded or invaded soils suggest different potential mechanisms of invasion facilitation. These findings are consistent with the hypothesis that non‐native plant species that dominate landscapes may “cultivate” a different soil pathogen community to their rhizosphere than those of rarer native species. This article summarized work designed to assess communities of soil pathogens associated with invasive and noninvasive wetland genotypes of Phragmites australis. These results suggest that nonindigenous plant species that dominate landscapes may “cultivate” a different soil pathogen community to their rhizosphere than those of rarer indigenous species.